Pharmaceutical Sciences Encyclopedia 2011
DOI: 10.1002/9780470571224.pse430
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antimicrobial Peptides as Therapeutic Agents

Abstract: Classical antibiotics work by inhibiting bacterial cell wall synthesis, protein synthesis, DNA (deoxyribonucleic acid) replication, or by modifying metabolism. Bacteria can resist antibiotics as a result of chromosomal changes (mutation or inductive expression of a latent chromosomal gene) or the exchange of genetic material via plasmids and transposons. As this chapter will discuss, antibiotics are rendered inactive by three major mechanisms: (1) antibiotic inactivation by destruction or modification, (2) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 397 publications
1
14
0
Order By: Relevance
“…The amphipathicity values of our AMPs are similar to those observed for native AMPs in the length of 22–27 residues (see review by Hodges et al, 2012). 16 In summary, both amphipathicity and the inducible α -helical structure play a critical role in providing AMPs with the desired properties.…”
Section: Resultsmentioning
confidence: 99%
“…The amphipathicity values of our AMPs are similar to those observed for native AMPs in the length of 22–27 residues (see review by Hodges et al, 2012). 16 In summary, both amphipathicity and the inducible α -helical structure play a critical role in providing AMPs with the desired properties.…”
Section: Resultsmentioning
confidence: 99%
“…Hemolysis of human red blood cells is commonly used for in vitro assessment of AMP toxicity to normal cells. Many variations of this assay exist and inconsistency in red blood cells source, peptide exposure time and reporting of peptide concentrations impede comparison of AMP toxicity [ 57 ]. The length of time erythrocytes are exposed to AMPs during the hemolysis assay is the least standardized parameter of the method and the most commonly cited times are 30 min [ 58 , 59 , 60 ] and 1 hour [ 33 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cationic AMPs of the α‐helical class have two unique features: a net positive charge of at least +2 and an amphipathic character, with a non‐polar face and a polar/charged face (6). In our recent review of α‐helical AMPs, we found that the vast majority of peptides contain between 3 and 10 positively charged residues with a positive charge density of 1–3 positively charged residues for every 10 residues in the peptide (7). The largest number of amphipathic α‐helical AMPs are in the range of 22–27 residues in length (7).…”
mentioning
confidence: 99%
“…In our recent review of α‐helical AMPs, we found that the vast majority of peptides contain between 3 and 10 positively charged residues with a positive charge density of 1–3 positively charged residues for every 10 residues in the peptide (7). The largest number of amphipathic α‐helical AMPs are in the range of 22–27 residues in length (7). Also, it is thought that the development of resistance is considerably reduced with membrane‐active peptides whose sole target is the cytoplasmic membrane and whose interactions with membrane components are non‐specific.…”
mentioning
confidence: 99%